Jigsaw as a curriculum strategy to enhance pre-service teachers' understanding of economics calculations - Mochina W. Mphuthi (AOSIS, 2023)
Background: Economics is a discipline that ought to explain the world and its complexities, a social science that studies human behaviour and decision-making. Both learners and aspiring pre-service teachers (PST) who want to teach economics education view economics as complex. Pre-service teachers lack the necessary mathematical skills and feel intimidated by the quantitative nature of economics. As a result, they struggle to understand and apply economic concepts and to teach effectively. Hence, there is a need to learn new actionable approaches and strategies in teaching and learning in the economics classroom. Aim: The study aims to explore the use of Jigsaw puzzle games as a curriculum strategy (CS) to augment PSTs' understanding of teaching calculations in the economics classroom. Setting: The study looks at economics calculations through the lens of architecture theory. the study takes place on campus in the economics lecturer room where pre-service teachers attend economics classes. Methods: The study explored the discussions including the observations of six PSTs using a qualitative approach. Critical discourse analysis was used to analyse data. Results: Findings revealed that participants found the Jigsaw extremely insightful and interesting. They were further amazed by its ability to ignite critical and deep thinking to arrive at the right solution. Conclusion: The study concludes that introducing Jigsaw as a CS for PSTs can significantly improve their ability to teach calculations and concepts in economics effectively and actively. Contribution: The study has implications on how PSTs can engage in gamification while learning and demystifying the power of complexity in economic calculations.